2015
DOI: 10.1098/rstb.2014.0327
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of viruses and cells: do we need a fourth domain of life to explain the origin of eukaryotes?

Abstract: The recent discovery of diverse very large viruses, such as the mimivirus, has fostered a profusion of hypotheses positing that these viruses define a new domain of life together with the three cellular ones (Archaea, Bacteria and Eucarya). It has also been speculated that they have played a key role in the origin of eukaryotes as donors of important genes or even as the structures at the origin of the nucleus. Thanks to the increasing availability of genome sequences for these giant viruses, those hypotheses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 96 publications
2
41
1
Order By: Relevance
“…The monophyly of NCLDVs is not recovered in the cellular/NCLDV RNAP tree: NCLDVs do not form a fourth domain of life, as proposed by some 20 , nor nest among eukaryotes 24 . While some genes in the NCLDV genomes might have been recruited from different sources, notably their modern hosts and bacteria, we have shown that a congruent vertical evolutionary history of NCLDVs is traceable and sound.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The monophyly of NCLDVs is not recovered in the cellular/NCLDV RNAP tree: NCLDVs do not form a fourth domain of life, as proposed by some 20 , nor nest among eukaryotes 24 . While some genes in the NCLDV genomes might have been recruited from different sources, notably their modern hosts and bacteria, we have shown that a congruent vertical evolutionary history of NCLDVs is traceable and sound.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, it has been proposed that the giant pandoraviruses are related to members of the Phycodnaviridae 22 , but this grouping was not recovered in a recent phylogeny based on their DNA polymerases 23 . According to some studies, the different families of the NCLDVs emerged during the diversification of modern eukaryotes 24 , whereas in other studies, NCLDVs form a monophyletic group branching between Archaea and Eukarya 29 /10/2018 13:51:00. Some authors have even suggested that several families of giant viruses could have originated independently from extinct cellular lineages, possibly even before the last universal common ancestor (LUCA) of Archaea, Bacteria, and Eukarya 11,25 .…”
mentioning
confidence: 99%
“…Viral homologues branched outside the eukaryotic clade in early trees, suggesting that an ancient Megavirus, perhaps part of a 'fourth domain' of life, might have donated these genes to the ancestral eukaryote [67]. Moreira & Ló pez-García [65] note that placing viruses in phylogenetic trees is exceptionally challenging because of their high rates of sequence evolution, which-not unlike the deep divergences between the cellular domains-can induce artefacts such as long-branch attraction, the spurious grouping of fast-evolving sequences due to chance convergences in the substitution process. Their new analyses, in combination with a review of recent work, lead them to suggest that the presence of eukaryotic genes on viral genomes is best explained by horizontal acquisition from their eukaryotic hosts.…”
Section: How Good Are Our Methods For Inferring the Past?mentioning
confidence: 99%
“…It has been proposed that giant viruses constitute remnants of ancient cellular life or are derived from an enigmatic fourth domain of life (3,7,8). Alternatively, evidence of signature cellular genes acquired from hosts implies that these viruses evolved from much smaller viral ancestors (6,9,10). Discovery of a virus encoding translation machinery that is more complete than in previously identified giant viruses would allow a comprehensive phylogenetic assessment of these signatures of cellular life to discriminate between these two hypotheses.…”
mentioning
confidence: 99%